ATHEISM IN ALAIN DE BOTTON'S ESSAYS IN LOVE - Lusia Kristiasih Dwi P.; Yobi Sardiyanto (Universitas PGRI Madiun, 2013)
This study aims at describing the influence of atheism to the main character's morality as well as describing the frailty of his atheism. This literary study belongs to qualitative research. In conducting this study, philosophical approach is employed to analyze atheism found in the novel.The main character does not believe the existence of God as he refuses to believe that everything happens in his life is predetermined or fated by God. He considers God as a myth, which does not truly exist. He also considers religion as a mere illusion created by human mind to keep them strong in facing hard and miserable life. Atheism gives influence to his morality as he does not consider God as the lawgiver. His moral judgment is based on utilitarian ethics in which the moral of an action should be judged by the consequence it entails. Such a relative moral judgment may offer a better concern for humanism. However, his relative judgments can be the frailty of his atheism since his moral judgments become unwise when he is under negative feeling such as sadness and desperation. Under negative feeling, his atheist's morality may approve his immoral action which leads to self-destruction.